Short-time compensation as a tool to mitigate job loss? Evidence on the US experience during the recent recession - Katharine G. Abraham; Susan N. Houseman (W.E. Upjohn Institute for Employment Research, 2013)
During the recent recession only 17 states offered short-time compensation (STC) - pro-rated unemployment benefits for workers whose hours are reduced for economic reasons. New federal legislation will encourage the expansion of STC. Exploiting cross-state variation in STC, we present new evidence indicating that jobs saved during the recession as a consequence of STC could have been significant in manufacturing, but that the overall scale of the STC program was generally too small to have substantially mitigated aggregate job losses in the 17 states. Expansion of the program is necessary for STC to be an effective counter-cyclical tool in the future.
Keywords: J65; J08; J20; 330; short-time compensation; work sharing; unemployment insurance; manufacturing